Internação contra a vontade de pessoas que usam substâncias psicoativas no Brasil: relações entre Poder, Direito e Verdade - Barbosa, Amanda Souza (Universidade do Vale do Rio dos Sinos, 2015)
The theme of this dissertation is the compulsory hospitalization of people who use psychoactive substances, especially drug addicts, which was approached from three main pillars: Philosophy, Bioethics and the Civil-Constitutional Law. It’s main objective is to analyze critically, after the identification of the main discursive models about the (in)adequacy of the compulsory hospitalization of people who use psychoactive substances, the social, legal and bioethical implications that taking medical-legal decisions in this topic involves in Brazil, under a transdisciplinary perspective, based on biopower and that observe the prohibitionist and stigmatizing treatment of these subjects, admittedly vulnerables. The research was developed according to the dialectical methodology. In terms of research techniques, bibliographical and documentary research was conducted. The dissertation structure is composed by two parts: the first one presents the status quo of compulsory hospitalization in Brazil, while the second is devoted to speeches that invalidate this status quo. On the first chapter of the first part was realized a study of the legal and regulatory treatment given to the institute. On the second chapter, the writings of Foucault about biopower were explored as a way to demonstrate the power relations that underlie this phenomenon. On the second part, the brazilian Psychiatric Reform’s lessons were rescued and the discursive models about the (in)adequacy of compulsory hospitalization were presented on the first chapter. They are: discursive model of wide acceptance, restricted acceptance and reprobation. On the second and final chapter of development part, it aims to identify the successive violations of fundamental rights of people who use psychoactive substances, especially those living on the streets. Alterity was pointed as a necessary way to break the process of truth-inequality-exclusion of these people. Knowing that the belief in the addict's inexorable decision-making disability consists in the basis of speeches that bets on this treatment measure, the current incapacity theory of the Civil Code was questioned from the perspective of Civil-Constitutional Law, in the light of personal rights and Protective Bioethics. On the final considerations the main implications of making medical-legal decisions about compulsory hospitalization of people who use drugs were presented in the social, juridical and ethical plans, in response to the research problem. It was concluded that the compulsory hospitalization must be exceptional and a short-term one, for the sole purpose of detoxification. The government should invest in alternatives of out-of-door and voluntary treatments, since the Psychiatric Reform demonstrates that devices that isolate the patient produces social exclusion and vulnerability. The evaluation of the decision-making capacity of a patient must be individual and take into account not only autonomy but also the vulnerability factors to which the patient is exposed. Also, it was identified the need for a national observatory on drugs, which not just gather scientific studies as OBID already does, but that can produce knowledge for a better understanding of the phenomenon, maintaining constant dialogue with universities, health professionals, patients and their families.
Keywords: Drogas; Internação; Biopoder; Capacidade; Exclusão; Drugs; Hospitalization; Biopower; Capacity; Exclusion; ACCNPQ::Ciências Sociais Aplicadas::Direito